2001
DOI: 10.1086/321961
|View full text |Cite
|
Sign up to set email alerts
|

Multichronometric Evidence for an In Situ Origin of the Ultrahigh‐Pressure Metamorphic Terrane of Dabieshan, China

Abstract: A B S T R A C TU-Pb zircon data on gneisses indicate a Late Proterozoic protolith at ∼700 Ma at Bixiling and a Late Archean to Early Proterozoic for the Shuanghe sheet within the ultrahigh-pressure metamorphic terrane of Dabieshan (China). U-Pb zircon and Sm-Nd dates on the gneisses of the Shuanghe sheet constrain a metamorphic peak at ∼230 Ma. Rb-Sr and 40 Ar-39 Ar analyses of phengite from five gneisses in the Bixiling Complex yield ages at 198-212 Ma, overlapping the 190-220-Ma age on eclogites. The host gn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 46 publications
8
36
0
1
Order By: Relevance
“…Firstly, detrital zircons from a metasedimentary rock show two peak ages of ~1.96 and ~1.39 Ga, suggesting that the Yangtze craton not only experienced Paleoproterozoic reworking and Neoproterozoic continental crustal growth [4], but also underwent Mesoproterozoic magmatic activity whose nature needs to be further determined. Secondly, the metamorphic ages of 837 ± 8 Ma and 818 ± 10 Ma on zircon overgrowth rims are obtained from a dioritic gneiss and a metasedimentary rock, which are similar to the metamorphic zircon age of 834 ± 31 Ma for a calc-silicate rocks reported by Zhang et al [28] and also the amphibole 40 Ar/ 39 Ar age of 818 ± 10 Ma obtained for amphibolite by Shen et al [29]. This indicates that the main phase amphibolite facies metamorphism of the Douling Complex occurred during the Neoproterozoic, which is still unreported for the Yangtze craton.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Firstly, detrital zircons from a metasedimentary rock show two peak ages of ~1.96 and ~1.39 Ga, suggesting that the Yangtze craton not only experienced Paleoproterozoic reworking and Neoproterozoic continental crustal growth [4], but also underwent Mesoproterozoic magmatic activity whose nature needs to be further determined. Secondly, the metamorphic ages of 837 ± 8 Ma and 818 ± 10 Ma on zircon overgrowth rims are obtained from a dioritic gneiss and a metasedimentary rock, which are similar to the metamorphic zircon age of 834 ± 31 Ma for a calc-silicate rocks reported by Zhang et al [28] and also the amphibole 40 Ar/ 39 Ar age of 818 ± 10 Ma obtained for amphibolite by Shen et al [29]. This indicates that the main phase amphibolite facies metamorphism of the Douling Complex occurred during the Neoproterozoic, which is still unreported for the Yangtze craton.…”
Section: Discussionsupporting
confidence: 79%
“…Similar age data were formerly reported in the Dabie-Sulu region. For example, the crystallization age of 2493 ± 13 Ma [38] was obtained for the TTG gneiss underlying the Zhangbaling Group in the eastern Anhui province, and the upper intercept age of 2458 ± 76 Ma [39] was recorded in zircon from the Shuanghe gneiss in the Dabie Mountain. Also in the Dabie Mountains, Chen et al [40] reported another upper intercept zircon age of 2489 ± 25 Ma from an eclogite.…”
Section: Discussionmentioning
confidence: 99%
“…3(a), (b), (d)). Interestingly, these ages fall within, but somewhat later than, the Dabie UHP metamorphic event from 245 to 225 Ma (Ames et al, 1993(Ames et al, , 1996Li, S.-G. et al, 1993Li, S.-G. et al, , 1994Li, S.-G. et al, , 1999Li, S.-G. et al, , 2000Chavagnac and Jahn, 1996;Rowley et al, 1997;Hacker et al, 1998;Chavagnac et al, 2001;Ayers et al, 2002;Zheng et al, 2003b). Amphibolite-facies retrogression may be a major reason to zircon overgrow and associated resetting of U-Pb system to Early Jurassic ages Zheng et al, 2003c).…”
Section: Early Mesozoic Metamorphismmentioning
confidence: 85%
“…But the occurrence of granulite-facies rocks in North Dabie but their absence in South Dabie indicate that the two units experienced differential histories of exhumation subsequent to the peak UHP metamorphism (Zheng et al, 2001). Paleoproterozoic to Archean ages were reported to occur in zircons from the North Dabie granulite-facies rocks (Chen et al, 1996;Jian et al, 1999;Wu et al, 2002) and the South Dabie UHP parametamorphic rocks (Chavagnac et al, 2001;Ayers et al, 2002;Chen et al, 2002Chen et al, , 2003. This indicates the presence of very old basement in the northern margin of the Yangtze Block and thus its involvement during continental deep subduction.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation